(3S, 4S)‐N‐substituted‐3, 4‐dihydroxypyrrolidines as ligands for the enantioselective Henry reaction. (20th January 2021) - Rénio, Márcia R.R.; Sousa, Francisco J.P.M.; Tavares, Nélia C.T.; Valente, Artur J.M.; da Silva Serra, M. Elisa; Murtinho, Dina
Abstract : The enantioselective Henry reaction is a very important and useful carbon–carbon bond forming reaction. The execution of this reaction requires the use of efficient chiral catalysts. In this work, in situ formed complexes of N ‐substituted dihydroxypyrrolidines, chiral ligands derived from L‐tartaric acid and amines, were evaluated as catalysts in the enantioselective Henry reaction. The results showed that the nature of the N ‐substituent on the ligand significantly influences the outcome of the reaction. Best results were obtained using a Cu (II) complex of (3 S, 4 S )‐ N ‐benzyl‐3, 4‐dihydroxypyrrolidine, in the presence of DIPEA, for the reaction of aromatic aldehydes with nitromethane, at room temperature, originating products with er up to 92:8 ( R : S ) and conversions up to 96%. The interaction between the pyrrolidine ligand and the copper ion, in isopropanol, was followed by UV‐vis spectrophotometry, showing a 1:1 stoichiometry and a binding constant of 4.4. The results obtained will contribute to the design and development of more efficient chiral catalysts for this type of reaction. Abstract : N ‐substituted‐dihydroxypyrrolidine chiral complexes were prepared and evaluated in the enantioselective Henry reaction of aromatic aldehydes with nitromethane. The reaction outcome was dependent on the N ‐substituent of the ligand. Conversions and er up to 96% and 92:8 ( R : S ), respectively, were obtained using Cu(II)‐(3S, 4S)‐ N ‐benzyl‐3, 4‐dihydroxypyrrolidine. Pyrrolidine–copper interaction occurs through a 1:1 stoichiometry (binding constant:4.4).